Chinese or Malay-Medium Schools? A Study of Factors Influencing Chinese Parents’ Choice of Primary Schools in Sarawak, Malaysia - Diana Phooi-Yan Lee; Su-Hie Ting; May-Chiun Lo (Kajian Malaysia, 2017)
This study examined factors that influence Chinese parents' choice of medium in primary schools in Sarawak, Malaysia. A questionnaire that was based on the Theory of Planned Behaviour was administered to investigate the influence of attitudes towards school, social pressure (subjective norms) and perceived behavioural control on parents' intentions for school choice. The survey was conducted with 397 Chinese respondents who had children in one of 21 Chineseand Malay-medium schools in Kuching, Sarawak. The results showed that the strongest influence on primary school choice was perceived behavioural control, which is the extent to which parents felt capable of paying fees and enrolling their children in the school of their choice. Positive attitudes towards Chinese schools also predicted choice for Chinese-medium schools. Parents who wanted their children to learn Mandarin and Mathematics and to have a Chinese cultural appreciation chose Chinese-medium schools. However, subjective norms had little influence on school choice. Collectively, attitudes, subjective norms and perceived behavioural control accounted for 44.0% and 32.4% of the variance in Chinese parents' intentions to choose Chinese- and Malay-medium schools, respectively. The findings suggest that there may be other factors that influence school choice, which should be investigated using interviews.